Koping stres keluarga Suku Batak Toba dengan anak infertilitas primer - Sormin, Tumiur (JOURNAL OF Mental Health Concerns, 2023)
Background: In the 2018 Consensus on Infertility Management, HIFERI 2013 reported that the prevalence of infertility in Indonesia was 21.3 percent. Of the 39.8 million couples of childbearing age (PUS) in Indonesia, 10–15 percent of them are declared infertile and an estimated 4–6 million couples require infertility treatment to have children. Based on Silaban's 2008 research, wife infertility in the Batak people is treated as something that demeans the dignity and perfection of the husband, so that at traditional weddings parents and relatives always convey their wishes and hopes that the newly formed couple will have many children. Purpose: This study aims to determine the stress coping of Toba Batak families with primary infertility children in Bandar Lampung in 2018. Methods: This research is a qualitative research with a phenomenological approach. Information was obtained by conducting in-depth interviews, FGDs and observations. Informants in this study consisted of 6 main informants, 3 triangulation informants. Results: The results of this study indicate that families begin to experience symptoms of stress after 3 years of their children being married without children. Conclusion: Psychological stress experienced is inferior and feels insignificant. Social stress is feeling of not being elder in adat and clan groups. Economic stress makes it difficult to pay for doctor's examinations and buy medicine. Physical stress can not sleep and lack of mood with husband. Religious stress sometimes considers God unfair. The stress coping used by the family is seeking social support, special prayer for the mother's younger brother, avoiding routine activities, positive assessment by visiting recreation and special prayer, accepting responsibility by confiding in families who are successful in infertility therapy and solving concrete problems such as program plans. test-tube baby. Suggestion: For families who experience this to keep fighting, good luck and success, everything is beautiful in its time.   Keywords: Stress Coping; Batak Tribe; Primary Infertility.   Pendahuluan: Dalam Konsensus Penanganan Infertilitas 2018, HIFERI 2013 melaporkan bahwa prevalensi infertilitas di Indonesia sebesar  21,3 persen. Dari 39,8 juta pasangan usia subur (PUS) di Indonesia, 10–15 persen diantaranya dinyatakan infertile dan diperkirakan 4–6 juta pasangan memerlukan pengobatan infertilitas untuk mendapatkan keturunan.  Berdasarkan penelitian Silaban 2008, kemandulan istri pada masyarakat suku Batak, disikapi sebagai sesuatu yang merendahkan martabat dan kesempurnaan suami, sehingga pada acara adat perkawinan orangtua dan kerabat selalu menyampaikan keinginan dan harapannya supaya pasangan yang baru membentuk rumah tangga itu mendapat banyak anak . Tujuan: Penelitian ini bertujuan untuk mengetahui koping stres keluarga suku Batak Toba dengan anak infertilitas primer di Bandar Lampung tahun 2018. Metode: Penelitian ini merupakan penelitian kualitatif dengan pendekatan fenomelogi. Informasi diperoleh dengan melakukan wawancara mendalam, FGD dan observasi. Informan dalam penelitian ini terdiri dari 6 orang informan utama, 3 informan triangulasi. Hasil: Hasil dari penelitian ini menunjukkan  bahwa keluarga mulai mengalami gejala stres setelah 3 tahun anaknya menikah belum memiliki anak. Simpulan: Stres psikologi yang dialami adalah minder dan merasa tidak berarti. Stres sosial merasa tidak dituakan di adat dan kumpulan marga. Stres ekonomi kesulitan membayar pemeriksaan dokter dan membeli obat. Stres fisik tidak bisa tidur dan kurang mood dengan suami. Stres religi kadang menganggap Tuhan tidak adil. Koping stres yang digunakan keluarga adalah mencari dukungan sosial doa khusus adik laki-laki ibu,  menghindar dengan kegiatan rutin, penilaian positif dengan mengunjungi rekreasi dan berdoa khusus,  menerima tanggung jawab dengan curhat pada keluarga yang sukses terapi infertilitas dan penyelesaian masalah secara konkret  seperti rencana program bayi tabung. Saran: Kepada keluarga yang mengalami hal tersebut untuk tetap berjuang, semoga sukes dan  berhasil,  semua indah pada waktunya.